2011
DOI: 10.1371/journal.pone.0020560
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Gene Regulatory Networks in Amnion Cells Following Cytokine Stimulation: Translational Systems Approach to Modeling Human Parturition

Abstract: A majority of the studies examining the molecular regulation of human labor have been conducted using single gene approaches. While the technology to produce multi-dimensional datasets is readily available, the means for facile analysis of such data are limited. The objective of this study was to develop a systems approach to infer regulatory mechanisms governing global gene expression in cytokine-challenged cells in vitro, and to apply these methods to predict gene regulatory networks (GRNs) in intrauterine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 152 publications
2
17
0
Order By: Relevance
“…The expression of these genes, PTGS2, BMP2, NAMPT and CXCL2, increases during fetal membrane activation at labour (Haddad et al 2006, Johnson et al 2006, Mazaki-Tovi et al 2008, Li et al 2011, Lim et al 2012. Their promoters are rich in CpG motifs, which form clusters called CpG islands.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression of these genes, PTGS2, BMP2, NAMPT and CXCL2, increases during fetal membrane activation at labour (Haddad et al 2006, Johnson et al 2006, Mazaki-Tovi et al 2008, Li et al 2011, Lim et al 2012. Their promoters are rich in CpG motifs, which form clusters called CpG islands.…”
Section: Discussionmentioning
confidence: 99%
“…Array-based studies assessing the expression of a large number of genes simultaneously as well as studies determining the expression level of proinflammatory candidate genes have shown that the activity of many inflammatory genes increases at term even in the absence of histological inflammation or detectable infectious insult (Haddad et al 2006, Johnson et al 2006, Mazaki-Tovi et al 2008, Li et al 2011, Lim et al 2012. This changing pattern of gene expression has been described as an 'acute inflammation gene expression signature' (Haddad et al 2006), which transforms the membranes into an activated state producing uterotonic stimulants such as prostaglandins and undergoing structural remodelling in preparation for rupture during labour.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The novel paradigm of “systems biology” provides a promising opportunity to overcome these restrictions and improve our understanding of the key molecular pathways that initiate labour in women [6]. Systems biology provides useful strategies to integrate the complex interactions within biological systems through building computational models.…”
Section: Introductionmentioning
confidence: 99%
“…There is a paucity of data on IRFs and human labor; although a recent publication demonstrated that using microarray analysis, IRF1 mRNA expression was increased following IL1B challenge in primary human amnion cells [33]. We hypothesized that 1) human labor and delivery would be associated with increased IRF1 expression in fetal membranes and/or myometrium, 2) proinflammatory stimuli would increase IRF1 transcriptional activity, and 3) inhibition of IRF1 using small interfering RNA (siRNA) would be associated with decreased expression and secretion of proinflammatory cytokines in the presence of infection or inflammation.…”
Section: Introductionmentioning
confidence: 99%